THE PRICE OF FLAVOR: BRONCHIOLITIS OBLITERANS DUE DIACETYL, VAPING, AND OCCUPATIONAL EXPOSURE - Katarzyna Krupa; Weronika Głowacz; Anna Daniel; Kacper Jankowski; Aleksandra Maciejczyk; Natalia Kraciuk; Alicja Bury; Karol Bartecki; Julia Błoniecka; Małgorzata Piekarska-Kasperska (International Journal of Innovative Technologies in Social Science, 2025)
Background. Bronchiolitis obliterans (BO), or “popcorn lung,” is a rare, irreversible obstructive lung disease involving inflammation and fibrosis of small airways. Initially linked to occupational diacetyl exposure in the food industry, BO is now also associated with environmental toxins, post-transplant complications, and e-cigarette use. Aim. This review presents current knowledge on BO, focusing on pathogenesis, risk factors, clinical presentation, diagnosis, treatment, and public health implications, particularly concerning e-cigarettes and environmental exposures. Materials and Methods. A narrative review was performed using PubMed, Scopus, ScienceDirect, and Google Scholar, screening English and Polish-language articles from 2000–2025. Keywords included: “bronchiolitis obliterans,” “diacetyl,” “e-cigarettes,” “vaping,” “occupational exposure,” and “BO diagnosis.” Studies involving humans, relevant animal models, or in vitro analyses were included. Analysis of Literature. BO often presents with nonspecific symptoms and is commonly underdiagnosed. High-resolution CT and histopathology are key diagnostic tools. While immunosuppressive therapy may help post-transplant patients, it is ineffective in toxin-induced BO. Supportive care, including bronchodilators, oxygen therapy, and rehabilitation, remains the mainstay of treatment. Lung transplantation is a last resort. E-cigarettes pose a growing risk due to vaporized compounds like diacetyl and formaldehyde. Conclusions. BO remains a serious clinical and public health challenge. With no curative treatment and poor prognosis in many cases, prevention is critical. Regulatory oversight of harmful inhaled substances, particularly in vaping products and occupational environments, alongside public education on associated risks, is essential.